THE RELATIONSHIP AMONG SELF-CONCEPT, READING ATTITUDE AND READING COMPREHENSION ACHIEVEMENT OF SINGLE PARENTED STUDENTS OF PUBLIC JUNIOR HIGH SCHOOLS IN DISTRICT OF ILIR BARAT I PALEMBANG - Rosdiana Surip (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2016)
THE RELATIONSHIP AMONG SELF-CONCEPT, READING ATTITUDE AND READING COMPREHENSION ACHIEVEMENT OF SINGLE PARENTED STUDENTS OF PUBLIC JUNIOR HIGH SCHOOLS IN DISTRICT OF ILIR BARAT I PALEMBANG Rosdiana Surip Junior High School No. 42, Palembang, South Sumatera ana.fadli@yahoo.co.id Abstract: This study investigated whether or not there were significant correlations between self-concept and reading comprehension achievement, and between reading attitude and reading comprehension achievement. The aims of this study were also to see whether or not students’ self-concepts and reading attitude gave significant contribution to reading comprehension achievement; whether there were significant correlations among students’ self-concept, reading attitude and reading comprehension achievement; and how much self-concept and reading attitude contributed to students’ reading comprehension achievement. One hundred and eighty-three single-parented students of Public Junior High Schools in District of Ilir Barat I Palembang, South Sumatera, were participated in this study. Self-Concept and Reading Attitude questionnaires and a reading comprehension test were used to collect the data. The results of this study revealed that there was a positive correlation between students’ self-concept and reading comprehension achievement and between students’ reading attitude and reading comprehension achievement. There was also a significant correlation among self-concept, reading attitude and reading comprehension achievement. Students’ self-concepts and reading attitude gave significant contribution (44.4%) to reading comprehension achievement. Keywords: self-concept, reading attitude, reading comprehension achievement